Antioxidant properties of a thermoultrasonicated cactus pear [Opuntia ficus indica (L.) Mill, (Cactaceae)] blend juice in comparison with traditional thermal processing - Ayala-Niño, Alexis; Cruz-Cansino, Nelly; Ramírez-Moreno, Esther; Sánchez-Franco, J. Antonio; Ariza-Ortega, J. Alberto; Calderón-Ramos, Zuli G.; Delgado-Olivares, Luis (Emirates Journal of Food and Agriculture, 2022)
Functional beverages market requires conservation methods where bioactive compounds could persist for their bioavailability. The aim of this work was determined the extractwion yield, antioxidant capacity and bioavailability of a cactus pear (Opuntia ficus-indica) juice blended using different solvent to extraction after pasteurization (PAST) or thermoultrasonication (TUS) treatment. The best properties were exhibited by TUS juice, showing 575.8 ± 11.1 mg GAE·L-1 for total phenolic, and 392.78 ± 4.1 mg betanain E·L-1 for pigment content. Which resulted in a greater antioxidant activity bioavailable (87% DPPH; 38% ABTS). The highest antioxidant activity was found in the TUS methanolic extraction, exhibiting higher bioaccessibility than the juice (78% ABTS; 179% DPPH). It can be concluded that thermoultrasonication and methanolic extraction of a cactus pear juice blend allows a greater antioxidant compounds to be bioavailable